Exploring the Causes of Learning Style Preferences in EFL College Students: A Comparative Case Study in Taiwan - I-Ju Chen; Hui-Jing Hsiao (An Overview of Literature, Language and Education Research Vol. 10, 2025)
This study investigated the learning styles of two college-level students of English as a Foreign Language (EFL) in Taiwan. Using a learning style preference checklist and semi-structured interviews, the researchers first used a questionnaire to explore the participants’ perceptional learning styles in terms of preferences and then interviewed participants’ underlying reasons for these preferences. As a qualitative study, two cases, each from different academic majors, revealed distinct preferences. The learner majoring in a business-related field favored the auditory learning style, while the participant with a design background preferred a haptic learning style. These findings suggest that a learner’s background may play a vital role in the development of their learning style. Additionally, learning preferences are likely shaped by educational experiences and peer interactions. Furthermore, style preferences in the EFL learning environment may evolve over time, vary across different contexts, and change with different tasks. The study may contribute to educators by underscoring the need for adaptive teaching strategies that consider students’ diverse backgrounds and hopefully enhance language learning outcomes to some extent.